Halal tourism development strategy for optimizing local revenue and economic growth in the tourism sector in Bangkalan Regency - Anshori, Mochammad Isa; Prasetyo, Alvin Sugeng; Kamil, Ahmad (Journal of Halal Product and Research (JHPR), 2023)
Sectoral economic development seen from the halal tourism sector is one sector that can encourage economic growth. This is the reason for the importance of developing a halal tourism development strategy to accelerate economic growth in Bangkalan Regency. In addition, the tourism sector is also an important source of revenue for local governments, namely Regional Original Revenue (PAD) in Bangkalan Regency. Regional Original Revenue is used to finance development in Bangkalan Regency so as to improve the welfare of its people and advance the region. This study uses the SWOT method to analyze the right development strategy for halal tourism in Bangkalan Regency. Therefore, the purpose of this study is to develop and analyze halal tourism development strategies for optimizing Regional Original Revenue and economic growth in the tourism sector in Bangkalan Regency.